Affrikatization *t’, *d’ > *ć, *ʒ’ in Western Pomerania in local and field names - Duma, Jerzy (Papers in Linguistics, 2022)
The article analyses the scope of the process of affricatization *t’, *d’ > *ć, *ʒ’ in Western Pomerania. Its gradual disappearance towards the west was confirmed – higher for the former *d’, smaller for the former *t’. In the old Slavic dialects of West Pomerania, as well as in the old Slavic dialects of Mecklenburg, East Holstein or in the dialect of Połabian Drzewians, there is no such affricatization in most local and field names, i.e. *t’ > t, *d’ > d. This may confirm the loss of accommodative pronunciation in these dialects. The lack of accommodative pronunciation before the vowels of the front row typologically brings these dialects closer to the following dialects and languages: Upper Sorbian, Czech and Slovak as well as the South Slavic languages. It is also partially similar the multiple of consonants before *e, *ě and *i in Ukrainian.